Soil organic carbon sequestration under pastures in Arid region - Hasson Ahmed; Jweeg Muhsin (Nature Environment & Pollution Technology, 2013)
Two sites in Iraq were choosen to study the affect of annual pasture and perennial grasses (C4). The perennial grass pastures had SOC stocks, 1.6 (Baghdad) and 1.4 (Babylon) times that of the annual pastures. Soil Organic Carbon (SOC) pools were 1.90, 2.97 and 2.88;for annuals, perennials and tagasaste at Baghdad site. At babylon the SOC pools were 2.7, 4.70 and 3.71;under annuals, perennials and tagasaste respectively.Estimated total C sequestration contribution to the resident soil organic C pool was 2.8 times greater for perennials and 2.7 times for tagasaste than annual pasture at the babylon deep-sand site. Both the sites were sampled to a depth of 1.6m. Perennial grasses in this region gnerally produced more above ground biomass than annual pastures. However the differences in biomass input are unlikely to be large enough to explain the high rate of sequestration of these perennials. We hypothesis that the perennial grasses promote fungi such as mycorriza that convert a greater proportion of liable carbon to stable humic forms than under annual pastures.
Keywords: Arid region; Carbon sequestration; Soil organic carbon